Injury Prevention in Pre-Primary and Primary Education: An Analysis of Teachers´ Perspectives and Expertise - Loudová Stralczynská, Barbora; Chroustová, Kateřina; Bílek, Martin; Chytrý, Vlastimil; Krčmářová, Tereza; Krátká, Jana (Revija za elementarno izobraževanje, 2025)
The article presents a study focused on the teaching staff and the impact of their occupational health and safety (OHS) teaching on pupils in pre-primary and primary education. A questionnaire survey was conducted among 227 teachers from eleven pre-primary and primary schools in Prague, Czech Republic in 2021. Pre-primary teachers rated themselves as more competent in OHS than teachers of primary education, although pre-primary children had a higher rate of injuries. More frequent OHS training did not affect teachers’ self-assessment but reduced child injury rates, especially if such training was completed more than once a year.
Keywords: Children’s Injury Prevention, Injury Incidence, Occupational Health and Safety, Pre-primary and Primary School, Teachers.